2016
DOI: 10.1002/poc.3550
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the side-group at C=N bridging bond of bis-aryl Schiff bases on the wavelength of absorption maximum of ultraviolet absorption spectra

Abstract: The compounds N-(benzylidene)-anilines XArCH=NArY (XBAY), N-(phenyl-ethylene)-anilines XArC(CH 3 )=NArY (XPEAY) and N-phenyl-α-phenylnitrones XArCH=N(O)ArY (XPNY) have bridging group CH=N, C(CH 3 )=N and CH=N(O) respectively, in which the C(CH 3 )=N has a side-group methyl CH 3 at carbon end and the CH=N(O) has a side-group O atom at nitrogen end. In this work, a series of XPEAY and XPNY were synthesized, and their longest wavelength maximum λ max (nm) of ultraviolet absorption spectra were measured. Then the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Cao group have systematically investigated the substituent effect on the UV absorption energy of substituted aryl Schiff bases with imine bridge group (C═N), and found that the influence rule of the substituents on 2 ends of the dipole were distinctive for different parent skeleton (summarized in Table ). This phenomenon was also confirmed by this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cao group have systematically investigated the substituent effect on the UV absorption energy of substituted aryl Schiff bases with imine bridge group (C═N), and found that the influence rule of the substituents on 2 ends of the dipole were distinctive for different parent skeleton (summarized in Table ). This phenomenon was also confirmed by this study.…”
Section: Resultsmentioning
confidence: 99%
“…Hammett parameter ( σ ), proposed by Hammett in 1937, is a well‐known molecular descriptor characterizing the ground‐state substituent effect. It has been extensively applied to the quantitative structure‐property relationship studies and exhibited good performances . The Hammett parameter for para‐position substituent is expressed as σ p , which consists of 2 parts, the inductive effect σ F and the resonance effect σ R .…”
Section: Experiments and Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hammett constant σ was widely used but was less successful in quantifying the UV absorption spectra of organic compounds. In 2008, Cao et al proposed excited‐state substituent constant σccex to express the contribution of substituent electronic effect to the excited‐state molecule, and then they used the σccex to quantify the UV absorption spectra of many kinds of compounds . They observed that the wave number ν max (cm ‐1 , ν max = 1/λ max ) of the longest wavelength maximum λ max (nm) of UV were mainly affected by the excited‐state substituent constant σccex for substituted benzene, stilbene, and conjugated polyene .…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the wave number ν max (cm ‐1 , ν max = 1/λ max ) of the longest wavelength maximum λ max (nm) of UV were mainly affected by the excited‐state substituent constant σccex for substituted benzene, stilbene, and conjugated polyene . Whereas the ν max of Schiff bases were affected by both σccex and σ because of having a polar bridging bond C=N . It should be noted that the bridging group CH=CH in stilbene XArCH=CHArY (abbreviated XSBY) is a symmetrical group (ie, its right and left ends all are the CH).…”
Section: Introductionmentioning
confidence: 99%